Parenting Stres Ibu Bekerja Pada Kesehatan Mental Anak - Kevin Vitoasmara; Meisye Eka Saputri; Nadia Larasati; Nur Kartika Putri; Oktaviana Ratnawati; Liss Dyah Dewi A (STIKes Ibnu Sina Ajibarang, 2024)
This study investigates the impact of parenting stress among working mothers on their children's mental health. In the modern context where many mothers choose to work outside the home, parenting stress has become a central issue affecting family well-being. This article outlines the factors influencing parenting stress, its effects on children's mental health, and practical implications for interventions at the family and community levels. Through this study, it is hoped that more effective strategies can be identified to support the psychological well-being of future generations.